Development of Digital Teaching Materials Using Problem Based Learning Models on Business Introduction Subject - Dionisius Sihombing; Albert Pauli Sirait; Boimin Sirait (CV. Pusdikra Mitra Jaya, 2024)
This research aims to develop digital teaching materials, an E-book for the Introduction to Business course based on the Project-Based Learning (PBL) model. The development procedure of the Business Introduction E-book using PBL is adapted from the ADDIE development model. Media experts provided a total score for all assessment items of 57.5, with an average score of 3.83. Content experts gave an excellent rating, with a total score of 86 and an average score of 4.30. It can be concluded that the digital teaching material, an E-book based on PBL, is suitable for use in the Introduction to Business course. The student questionnaire responses yielded a percentage of 86.15% for the aspect of enjoyment, 83.15% for student interest in using the E-Book, 82.65% for the aspect of attention, and 87.45% for the aspect of student engagement.